Utility of a very high IRT/No mutation referral category in cystic fibrosis newborn screening. Issue 8 (22nd June 2015) - Kay, Denise M.; Langfelder‐Schwind, Elinor; DeCelie‐Germana, Joan; Sharp, Jack K.; Maloney, Breanne; Tavakoli, Norma P.; Saavedra‐Matiz, Carlos A.; Krein, Lea M.; Caggana, Michele; Kier, Catherine; the New York State Cystic Fibrosis Newborn Screening Consortium
Summary Newborn screening for Cystic Fibrosis (CF) began in New York in October, 2002 using immunoreactive trypsinogen (IRT)/DNA methodology. Infants with at least one CFTR mutation or very high IRT and no mutations (VHIRT) are referred for sweat testing. In a preliminary analysis, we noted a very low positive predictive value (PPV) and preponderance of Hispanic infants in the group of infants with CF referred for VHIRT, which led to a decision to revise, but not eliminate, the VHIRT category. Automatic referral for specimens with VHIRT collected on the day of birth was eliminated, and the VHIRT threshold was raised from 0.2% to 0.1%. In this report, we describe outcomes from VHIRT referrals among 2.4 million infants screened between March 2003 and February 2013. Following the algorithm change, referrals decreased by 37.8% overall (annual mean 1, 485 vs. 923), and the VHIRT PPV improved (0.6–1.0%). The number of infants diagnosed has remained consistent at 1 in 4, 400 births. The proportion of Black/Hispanic/Asian/Other infants with confirmed CF, CFTR‐related metabolic syndrome (CRMS), or possible CF/CRMS was 21.3% in infants with 1–2 mutations, but 75.8% in the VHIRT group. In conclusion, although the PPV among VHIRT referrals remains low, had this category never been implemented, 24 infants with confirmed CF, and 9 infants with CRMS or possible CF/CRMS, most of whom were Hispanic, would have been missed over the 10 years. Information from this study may be helpful in assessing the need for the VHIRT category and algorithm changes in other screening programs. Pediatr Pulmonol. 2015; 50:771–780. © 2015 Wiley Periodicals, Inc.